Panuveitis following Vaccination for COVID-19. (19th May 2021) - Mudie, Lucy I.; Zick, Jon D.; Dacey, Mark S.; Palestine, Alan G.
ABSTRACT: Background : COVID-19 vaccination has been accompanied by reports of inflammatory events. This report details a case of panuveitis following vaccination for COVID-19 Case.Description : A 43 year old female developed panuveitis with decreased vision three days after her second dose of Pfizer-Biontech mRNA vaccine. The choroid was significantly thickened and there was anterior chamber and vitreous inflammation. Shortly after onset of ocular symptoms she was also found have an asymptomatic COVID-19 infection. Treatment with oral and topical corticosteroids resulted in improvement in the panuveitis, with a mild recurrence after the initial attempt to taper these drugs.Conclusion : This report demonstrates a likely occurrence of vaccine-related panuveitis secondary to the Pfizer-Biotech mRNA vaccine for COVID-19.